Nilai Akademik dapat Ditingkatkan Melalui Pengelolaan Stres pada Siswa SMA di Jakarta - Hirashita Tobing , Christine Masada (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2025)
This study aims to examine whether stress management (Y) contributes to improving students' academic performance (X). A quantitative approach was used with a survey and quasi-experimental one-group pre-test post-test design to analyze the cause-and-effect relationship. Data collection involved questionnaires, interviews, behavioral observations, and document analysis. The research followed a structured process: students completed a pre-test questionnaire, received treatment, and then completed a post-test questionnaire to assess changes in stress levels and academic performance. The treatment applied in this study included individual counseling services and informational services, which aimed to help students manage their stress effectively. Interviews, observations, and document analysis were also conducted to support data collection by identifying students who experienced stress and those who successfully managed it after the intervention. The hypothesis was tested using the T-test, which resulted in a Sig. (2-tailed) value of 0.000 < 0.05, leading to the rejection of H₀ and acceptance of H₁. Based on these findings, the researcher concluded that effective stress management significantly contributes to improving students' academic performance in school. This study highlights the importance of stress management strategies in enhancing students' learning outcomes.